Configuración óptima de redes de intercambiadores de calor para mejorar la eficiencia energética en la destilería de la empresa Casa Grande S.A. - Chilón Iglesias, Mirko Miguel (2018)
The aim of this thesis was to simulate the optimal configuration of a network of heat exchangers, from the mass and energy balances that are made in the process of production of ethyl alcohol in the company Casa Grande S.A. As it has researched the optimal configuration of heat exchangers and the minimum area required for the distillation of wine, using the energy integration software - HINT, V.2.2. The system considered consists of hot and cold streams entering and leaving the same, as well as hot and cold services available on the ground. The results have concluded that it is possible to obtain an optimal heat exchange configuration considering an approach or minimum temperature of 10 K fold between exchangers for hot and cold streams network, which allows it to meet the overall objective proposed in this thesis